2015
DOI: 10.1038/ni.3321
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor Nr4a1 couples sympathetic and inflammatory cues in CNS-recruited macrophages to limit neuroinflammation

Abstract: Molecular mechanisms linking the sympathetic stress response and inflammation remain enigmatic. Here we demonstrate that the transcription factor Nr4a1 regulates production of norepinephrine (NE) in macrophages, thereby limiting experimental autoimmune encephalomyelitis (EAE), a mouse model of multiple sclerosis. Lack of Nr4a1 in myeloid cells led to enhanced NE production, accelerated leukocyte infiltration to the central nervous system (CNS) and disease exacerbation in vivo. In contrast, myeloid-specific del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 63 publications
6
85
1
Order By: Relevance
“…Using a gating strategy that we have previously demonstrated consistently distinguishes MDMs and resident microglia after ICH (11,64,65), we are able to precisely follow the temporal evolution of macrophage transcriptional programs after an acute injury. Consistent with other disease models (66,67), MDMs initially express an array of inflammatory genes upon arrival to the injured brain known to contribute to ICH pathology including Il1b, Tnf, Ccl2, and Nlrp3. Over time, MDMs downregulate these inflammatory genes and upregulate genes that are related to hemoglobin degradation, efferocytosis, and cholesterol transport such as Hmox1, Axl, CD63, ApoE, and Abcg1.…”
Section: Discussionmentioning
confidence: 83%
“…Using a gating strategy that we have previously demonstrated consistently distinguishes MDMs and resident microglia after ICH (11,64,65), we are able to precisely follow the temporal evolution of macrophage transcriptional programs after an acute injury. Consistent with other disease models (66,67), MDMs initially express an array of inflammatory genes upon arrival to the injured brain known to contribute to ICH pathology including Il1b, Tnf, Ccl2, and Nlrp3. Over time, MDMs downregulate these inflammatory genes and upregulate genes that are related to hemoglobin degradation, efferocytosis, and cholesterol transport such as Hmox1, Axl, CD63, ApoE, and Abcg1.…”
Section: Discussionmentioning
confidence: 83%
“…[101][102][103] On the contrary, NOD2 deficiency increases TLR2-mediated activation of NF-κB and dysregulated TLR2 in NOD2-deficient mice causes the development of antigenspecific colitis. 104,105 Not only NOD2, many other NLRs play inhibitory roles in regulating the signaling of TLRs: for NLRX1 and NLRC3 via interfering with the TRAF6-NF-κB signaling; 61,106,107 for NLRC5 via interacting with and blocking phosphorylation of IκB kinase α (IKKα) and IKKβ; 59 for NRLP6 and NLRP12 via targeting MAPK and NF-κB activation; 108,109 for NLRC4 via downregulating TLR5-mediated antibody immune responses against flagellin. 110 These synergistic or antagonistic interactions across these three PRR families contribute to a cross-linked and finely tuned network of PRR signaling in response to the large repertoire of PAMPs and ensures the most effective and proper outcomes of innate immune responses.…”
Section: Interplay Across Different Prr Signaling Pathwaysmentioning
confidence: 99%
“…It is also shown that NR4A1 limits the production of norepinephrine in macrophages through recruitment of the CoRESThistone deacetylase complex to the Th promoter, thus inhibiting the pathogenesis of experimental autoimmune encephalomyelitis, outlining a novel molecular link between sympathetic stress response and inflammation. 59 Signal-specific regulation of inflammatory responses Post-translational modifications (PTMs) constitute an essential layer of regulation of innate inflammatory signaling via affecting the function and activity of existing signaling molecules at post-translational level. 60,61 The conventional PTMs such as ubiquitination and phosphorylation and unconventional PTMs such as methylation, acetylation and sumoylation target nearly all critical components of PRR signaling, such as receptors, adaptors, enzymes and transcriptional factors to modulate the quality of PRR signals.…”
Section: Molecular Regulation Of Innate Immunity and Inflammationmentioning
confidence: 99%
“…For example, in animal models of Th1 type-mediated autoimmune diseases such as rheumatoid arthritis, β 2 -AdR stimulation alleviates inflammation [41]. In contrast, NE released from macrophages reportedly promotes inflammation via α 1 - or α 2 -AdRs in an autocrine manner [42, 43]. As in our previous results showing that NE released from hepatic sympathetic nerves plays a critical role in preventing Fas-mediated hepatocyte apoptosis through IL-6 [10], our present results show that α 1 -AdR agonists alone exert a protective effect against cancer progression by inducing a potentially anti-inflammatory function of IL-6.…”
Section: Discussionmentioning
confidence: 99%